Du Pastor Fido au saint constant : la transposition des codes de la pastorale dramatique dans le théâtre hagiographique français du XVIIe siècle - Anne Teulade (Etudes Epistémè)
This essay deals with some French hagiographic plays which do not rely on a tragic pathetic aesthetic, such as Corneille’s Polyeucte and Théodore. They are frequently considered as incoherent works, since they do not respect the classical rules. This paper shows that it is fruitful to compare them to pastoral dramas. The first part is devoted to the way the playwrights insert a pastoral place in the religious dramas. The space is then represented as dual, and it conveys ideological values: the pastoral place is clearly connected with a religious way of life. The second part presents a dramatic analysis of the plays. The plots integrate pastoral structures, and the treatment of love reminds the reader of Guarini’s Pastor Fido. As a consequence, the third part reveals why pastoral and hagiographic drama present such similarities: the faithful shepherd and the constant saint both represent the unique pole of fixity of a baroque world in which movement and instability prevails.